Artificial Intelligence Security in Multiple-Unmanned System Cooperation - Shi Wen (《中国工程科学》杂志社, 2021)
Multiple unmanned system cooperation is an important component of China’s new-generation artificial intelligence (AI) planning and it is a transformative technology for future national defense construction and social development of China. Although significant achievements have been made regarding the technological research and system integration of multiple unmanned system cooperation, research on AI security is still in its infancy. Promoting multiple unmanned system cooperation enables AI application and risk control. In this article, we propose a four-in-one strategy to promote the collaborative and secure development of multiple unmanned systems, investigate potential challenges and countermeasures for multiple unmanned system cooperation at the endogenous and derivative security levels, and propose several suggestions regarding the security of intelligent unmanned systems. Specifically, a national unmanned system verification platform should be established to promote the construction of talent teams; services need to be upgraded for the unmanned system industry to develop a new-generation AI security ecology; and the advantages of multiple unmanned system cooperation should be maximized to improve people’s livelihood.